Self-management activation for low back pain and its influencing factors among intensive care unit nurses: a multicenter cross-sectional study - Zeng, Zhi; Wan, Li; Yang, Xiuru; Yan, Fenglin; Liang, Zhenghua; He, Mei (Frontiers in Public Health, 2025)
ObjectiveTo investigate the current status of self-management activation of low back pain (LBP) among intensive care unit (ICU) nurses and analyze the influencing factors, to provide a reference for intervention strategies to improve their self-management activation of LBP.MethodsThrough a cross-sectional research method, 366 ICU nurses from five tertiary-level hospitals in Mianyang City were selected in January–March 2025 using a convenience sampling method. With ternary interaction determinism as the theoretical basis, the general information questionnaire, the Participants Activation for self-management of Back Pain (PAMQ), the presenteeism behavior scale, and the perceived social support scale (PSSS) scale were used to conduct the survey. Descriptive statistics, univariate analysis, and multiple linear regression analysis were employed to describe the current status of self-management activation for LBP among ICU nurses and to identify its associated factors.ResultsICU nurses scored (37.93 ± 5.69) on the PAMQ with a score of 69.0%, and the related self-management awareness, self-management beliefs, and self-management knowledge dimensions scored in the order of sub 75.1, 68.2, and 66.9%. Correlation analysis revealed that the self-management activation for LBP among ICU nurses was negatively correlated with presenteeism (p < 0.001) and positively correlated with perceived social support (p < 0.01). Multiple linear regression analysis showed that age, years of work experience, educational level, frequency of exercise, participation in LBP prevention training, presenteeism, and perceived social support were significantly associated with self-management activation for LBP among ICU nurses (p < 0.05), collectively explaining 63.6% of the total variance.ConclusionThe overall self-management activation for LBP among ICU nurses needs to be improved urgently. Although these nurses demonstrate a strong motivation for self-management, they possess insufficient knowledge regarding LBP. Therefore, future interventions should be tailored to key factors such as ICU nurses’ age, years of work experience, education level, exercise frequency, participation in LBP prevention training, presenteeism, and perceived social support. Developing such precise and systematic intervention strategies will enhance self-management activation for LBP, reduce the incidence of LBP, and ultimately promote the wellbeing of the nursing workforce.